Religion and Politics under the Būyids: The Case of al-Sharīf al-Murtaḍā and al-Sharīf al-Raḍī and the Development of Twelver Shīʿism - Hasan, Bayan (AUC Knowledge Fountain, 2025)
This thesis aims to explore the religion and politics of tenth and eleventh-century Baghdad, with a main focus on Twelver Shīʿī doctrine, by shedding light on one highly significant family that was central to the regulation of the ʿAbbāsid and Būyid government. The ʿAlid Mūsawī brothers, al-Sharīf al-Murtaḍā (d. 966/1044) and al-Sharīf al-Raḍī (d. 969/1015), were both influential figures amongst Baghdad’s scholastic community and were closely connected with the ruling elites. In this research, I examine three main activities that the brothers were involved in: their contribution towards Shīʿī law, the niqāba office, and Qur’ānic exegesis. My thesis shall examine a discrete number of religio-political functions of the Sharīf brothers. For this reason, I look at three spheres of activity: (i) their role in Shīʿī legal doctrine, mainly al-Sharīf al-Murtaḍā’s role as a jurist, where I will study his interaction with the Sunnī community through his legal text al-Intiṣār (ii) their position as nuqabā’, which often included other tasks, either with the government or the ʿAlid community. Within this activity, I will look at the appointment deeds of al-Sharīf al-Raḍī and his father, drafted by Abū Isḥāq al-Ṣābi’ (d. 384/994), and Abū al-Ḥasan al-Māwardī’s (d. 450/1058) text on Islamic governance to further understand the role of the naqīb and how lineage and relations with the ruling elites play an integral part to securing the position; and (iii) The interplay between juridical matters and the functions of the naqīb, where I study al-Murtaḍā’s legal treatise on governance. While these activities are mainly religious functions, they have an overlapping role with the politics of Būyid Baghdad, especially as the Mūsawī family had a close relationship with the ruling elites and served as their emissaries. Although the Būyids fostered a cosmopolitan environment for scholars in Baghdad during their reign, I argue that the Mūsawī family used the existing political tensions between the ʿAbbāsids and Būyids to their advantage to develop their doctrine. Additionally, their lineage and close relationship to the ruling elites was another factor that contributed towards this growth.